PEMILIHAN RASIO KEUANGAN TERBAIK UNTUK MEMPREDIKSI PERINGKAT OBLIGASI: STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEJ - Anna Purwaningsih (KINERJA, 2008)
This research aims at (1) finding financial ratios which can be employed to predict earning; (2) finding whether the financial ratio employed to predict bond rating is the best financial ratio to predict bond rating. Purposive sampling is put into use in collecting samples. There are 95 manufacture firms listed in BEJ as samples. The data analyzed in this research are data of audited financial reporting the year 1999-2005 and bond rating on Apri ls the year 2000-2006. Analysis methods employed in this research are (1) backward regression, to find financial ratios which can be applied to predict bond rating, and (2) factor analysis, to find the best financial ratio to predict bond rating. The best financial ratio is reflected in the value of factor loading. There are two main findings in this research, namely (1) financial ratios which can be applied to predict bond rating are SFA (productivity ratio), CFOTL (solvability ratio), and LTLTA and NWTA (the two are leverage ratio) (2) the best financial ratio to predict CACL (liquidity ratio) bond rating with loading factor valued 0.940.Keywords: financial ratio, earning, bond rating